Penerapan Metode Pembelajaran Student Active Learning (SAL) dalam Meningkatkan Kecerdasan Logis Matematis Siswa Kelas III SDN Kondangjaya III Karawang : Penelitian - Dienna Rachma Agniena; Siska Kusumawardani; Linda Astriani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the Application of the Student Active Learning (SAL) Learning Method in Improving the Logical Mathematical Intelligence of Class III Students of SDN.Kondangjaya III in 2024. The method used in this study is the Student Active Learning Learning Method. The results of the Classroom Action research conducted in two cycles showed that there was an increase in the use of SAL theory to improve Logical Mathematical Intelligence in fractional mathematics lessons. This can be proven from the results of PTK (Classroom Action Research), namely the highest Pre-Cycle score of 84.13 with 17.10% of students completing, the lowest score of 32.07 with 82.90% of students not completing, the average class score of 59.40, then the results of the Cycle 1 research were the highest score of 95.23 with 22.9% of students completing, the lowest score of 46.53 with 77.1% of students not completing. the average value of 66.07 and the last research, namely in cycle 2, obtained the highest value of 97.77 and the lowest value of 79.37 with students who completed 100% of learning, the average class value of 88.86. It can be concluded that the Application of the Student Active Learning (SAL) Learning Method in Improving Logical Mathematical Intelligence can improve learning outcomes in mathematics subjects in the field of fractions.